The untapped potential of early career researchers in academic publishing: Lessons learned from the Journal of Emerging Investigators model. Issue 3 (27th July 2022) - Otero, Claire E.; Osinski, Victoria; Mattison, Kari A.
Key points: The lack of formal training in peer review can be detrimental to the publishing activities of early career researchers, including graduate students and postdoctoral fellows. Lack of recognition of the work of early career researchers (ECRs) in review means that journals cannot easily identify them as potential reviewers in the future. Participation as peer‐reviewers increases understanding in early career researchers of their own writing and review process. ECRs can be highly motivated to volunteer for journal editorial work— Journal of Emerging Investigators encourages this by offering many different roles. Publishers that utilize and train early career researchers as peer‐reviewers can prevent poor reviewer practices.